Morphometry and Contents of the Suprascapular Notch with Potential Clinical Implications: Α Cadaveric Study - Tsikouris, George; Antonopoulos, Ioannis; Vasdeki, Dionysia; Chrysikos, Dimosthenis; Koukakis, Athanasios; Tsakotos, George; Georgakopoulos, Panagiotis; Troupis, Theodore (Journal of Brachial Plexus and Peripheral Nerve Injury, 2021)
Background The suprascapular notch (SN) represents the point along the route of the suprascapular nerve (SSN) with the greatest potential risk for injury and compression. Thus, factors reducing the area of the notch have been postulated for suprascapular neuropathy development.Methods Thirty-one fresh-frozen shoulders were dissected. The contents of the SN were described according to four types as classified by Polguj et al and the middle-transverse diameter of the notch was measured. Also, the presence of an ossified superior transverse scapular ligament (STSL) was identified.Results The ligament was partially ossified in 8 specimens (25.8%), fully ossified in 6 (19.35%), and not ossified in the remaining 17 (54.85%). The mean middle-transverse diameter of the SN was 9.06 mm (standard deviation [SD] = 3.45). The corresponding for type-I notches was 8.64 mm (SD = 3.34), 8.86 mm (SD = 3.12) was for type-II, and 14.5 mm (SD = 1.02) was for type III. Middle-transverse diameter was shorter when an ossified ligament was present (mean = 5.10 mm, SD = 0.88 mm), comparing with a partially ossified ligament (mean =7.67 mm, SD = 2.24 mm) and a nonossified one (mean = 11.12 mm, SD = 2.92 mm). No statistically significant evidence was found that the middle-transverse diameter depends on the number of the elements, passing below the STSL.Conclusion Our results suggest that SSN compression could be more likely to occur when both suprascapular vessels pass through the notch. Compression of the nerve may also occur when an ossified transverse scapular ligament is present, resulting to significant reduction of the notch's area.
Keywords: suprascapular notch; suprascapular nerve; neuropathy; morphometry; shoulder surgery; fresh frozen; cadavers